KORESPONDENSI BUNYI BAHASA LAMPUNG DIALEK TULANGBAWANG - NFN Roveneldo (Balai Bahasa Provinsi Riau, 2015)
This research discusses the differences of vowel correspondences, vowel, and consonant variations of Tulangbawang dialect of Lampung language in six research areas. The data collecting technique was conducted by applying dialectology method. Moreover, this research used the list of questions that listed in Swadeshs basic vocabularies. The result showed that there are differences in the linguistic elements in Lampung language which include the differences in phonology, morphology, and lexicon. In the phonological differences, it was found that there are one vowel correspondence, eleven vowel variations, and twenty three consonant variations. In general, vowel correspondence lies in the end of words, and the tendency of occurring is found in the research area 1, 3, 4, and 5. All research areas always have similarities but there are various changes for each correspondence in research area number six. In the morphological differences, there are differences in the form of suffixes namely correspondences. Besides, there are some lexical differences found in the six research areas.